Mal-estar entre professores em início de carreira diante de pressões do Saresp - Silva, Natália Menin da (Universidade Federal de São Carlos, 2020)
This study aims to comprehend the pressures faced by teachers in the beginning of their careers within the school environment while pursuing the bonus from Saresp (Evaluation System of Learning Performance of the State of São Paulo), and also to grasp which are the premises that benefit (or not) the valorization of those professionals. For this purpose, interviews were conducted with teachers who had up until five years of teaching experience in two state schools of basic education I and II, both in the city of São Carlos, SP. Those schools are used to receiving the Saresp bonus, a cash prize given to the teachers rewarding the “learning” of their students. The results were achieved through the qualitative methodology as a tool to analyze the interviews as well as its contents. In order to substantiate the research, Critical Theory and some of its thinkers were employed, especially regarding discussions of autonomy, emancipation and conformism. The study confirms that the pressures experienced by the teachers in the analyzed schools are in fact resulting from the state educational system’s demands, which end up causing tensions among the teachers who prepare their students to achieve Saresp’s desired goals. Such pressure initially causes a feeling of uneasiness, affecting newcomers, however, after some time of work, it can also be identified as an inherent feeling of the teaching/learning process, besides the “race” against time to meet the expectations of the bonus’ policy. It is clear the control of the administered world, which prescribes the teacher’s consciousness, making them relate with what has been imposed to them and meeting Saresp’s goals to receive the bonus, which forces said professionals to abide by the existing domination process. And even when teachers ponder about the damages caused by the oppressive work dynamics, through the impositions of the state educational system as well as other dynamics within the school, they don’t quit this identification with the prevailing values of a society that imposes such structure, emphasizing an adaptation to the dominant system. Consequently, the full training, in other words, the real education, which presents itself to the educational system as the possibility of emancipation and autonomy is, in fact, a semi education. Education moves away from its essential value, the real enlightenment. Thus, the teacher ends up conforming within the current situation and all of their pedagogical practices become exploited into this logic. Such pedagogical practices end up curbing the development of critical thinking and autonomy, which result in adaptation and conformism, in the other words, semi education.
Uneasiness among teachers in the beginning of their careers regarding Saresp’s pressures
Keywords: Professores em início de carreira; Política de Bônus; Formação; Semiformação; Emancipação; Newcomer teachers; Bonus policy; Education; Semi education; Emancipation; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL